Pengenalan Destinasi Wisata Rowo Jombor Melalui Psychofest Run Pada Komunitas Running Kabupaten Klaten - Anis Marjukah; Abdul Haris; Agung Nugroho Jati; Dandang Setyawanti; DB Putut Setiyadi (Cattleya Darmaya Fortuna, 2025)
The introduction activity of the Rowo Jombor tourist destination through the Pschofest Run aims to bring students closer to real practice in the management/governance of sports event organizations. This activity is in conjunction with the promotion activity of the new tourist destination Rowo Jombor Klaten which has been revitalized by the Central Java Provincial Government. The design of the activity is in the form of learning real practice of sports event management and tourism destination promotion practices. This activity is in collaboration with partners from the Tourism, Culture and Sports Department of Klaten Regency and the Klaten police station. Mentoring activities for the HMP Psychology student team were carried out for three full days before the implementation including: presentation of the vision, mission, objectives of the activity, activity flow, activity operation management, assistance in consulting on permits to related agencies, activity route tests were carried out through coordination with the Rowo Jombor tourist village manager. During the activity, sponsorship exploration of various institutions was carried out and at the final stage an evaluation of the activity was carried out. There was a participant satisfaction test from the results of the Psychofest Run activity management with the results of the questionnaire showing participant satisfaction and community satisfaction as well as village institutions around the Rowo Jombor tourist attraction. The outcome of the activity is obtained by the emergence of various post-activity results where students are able to become real initiators and movers of youth who are aware of tourism, aware of sports and aware of health through various events in the student's domicile area and in the village. After the Psychofest Run activity, it is necessary to carry out entrepreneurship training for village communities.